Captain Cook - Noonan, Jon (New York : Crestwood House, 1993)
Discusses the life and travels of the eighteenth-century British navigator and explorer known for his adventurous voyages and maps of the Pacific.
Includes index.
Keywords: Cook, James, 1728-1779 - Juvenile literature; Explorers - Great Britain - Biography - Juvenile literature; Explorers